Intention to consume insects as an alternative protein in food - Sheyla Maria Barreto Amaral; Matheus Calixto Saraiva; Rosenildo dos Santos Silva; José Danrley Moreira; Elisabeth Mary Cunha da Silva (Conexões: Ciência e Tecnologia)
This study aimed to know and understand the intention, by Brazilians (N = 510, ≥ 18 years old), of consuming insects as an alternative protein. An online survey was developed. It consisted of 24 questions, divided into three sections: socioeconomic data, knowledge about entomophagy, and consumption of insects in the human diet. The majority of respondents (90.78%) declared themselves omnivores and 45.88% stated that they do not intend to change their meat consumption. Moreover, several factors influence consumption, with a positive environmental perspective (N = 229) and a negative consumption habit (N = 298), since this practice is considered uncommon in the country and most respondents had never consumed insects (77.90%). The most adopted condition to consume insects was that they were not able to be seen with the naked eye (N = 252), and 32.94% of participants strongly agree that the best way to consume an insect-based food would be through the preparation of snacks. Despite these results, the majority of respondents (52.90%) indicated that they are able to purchase insect-based products if they were available in the market.